Розробка гри на ігровому рушії Unity - Єлтишев, П. І. (ХНУРЕ, 2024)
The report goes over a number of reasons why I chose Unity to develop a 2D platformer. I will receive a reliable game engine that will help quickly and efficiently realize all my ideas. This engine has a lot of features that help you create a new game from scratch. It uses the C# programming language, which makes it ideal for beginners and experienced programmers alike. Unity supports most platforms and has a large number of assets, which greatly simplifies the development process of any game and a large active community that helps developers solve problems.
Keywords: розробка гри; UNITY; game; IT-проєкт